Second-generation atrial tachycardias: adverse repercussions of ablation or a step in the right direction?. (April 2010) - Salukhe, Tushar V; Willems, Stephan; Steven, Daniel; Hoffmann, Boris A; Drewitz, Imke; Rostock, Thomas
Catheter ablation of atrial fibrillation (AF), particularly longer lasting AF, often requires extensive ablation within the atria and their annexed structures. Immediate procedural success is commonly defined as termination of AF during ablation. While this end point is associated with fewer AF recurrences and maintained sinus rhythm, recurrent atrial tachycardias are common and present a fresh challenge for the electrophysiologist. These atrial tachycardias are often more symptomatic than the initial AF, but are invariably more suited to mapping and ablation with an excellent prospect of maintained sinus rhythm.